Cysteines as Redox Molecular Switches and Targets of Disease - Fra, Annamaria; Yoboue, Edgar D.; Sitia, Roberto (Frontiers in Molecular Neuroscience, 2017)
Thiol groups can undergo numerous modifications, making cysteine a unique molecular switch. Cysteine plays structural and regulatory roles as part of proteins or glutathione, contributing to maintain redox homeostasis and regulate signaling within and between cells. Not surprisingly therefore, cysteines are associated with many hereditary and acquired diseases. Mutations in the primary protein sequence (gain or loss of a cysteine) are most frequent in membrane and secretory proteins, correlating with the key roles of disulfide bonds. On the contrary, in the cytosol and nucleus, aberrant post-translational oxidative modification of thiol groups, reflecting redox changes in the surrounding environment, are a more frequent cause of dysregulation of protein function. This essay highlights the regulatory functions performed by protein cysteine residues and provides a framework for understanding how mutation and/or (in)activation of this key amino acid can cause disease.